Intrafamilial variability of ZRS‐associated syndrome: characterization of a mosaic ZRS mutation by pyrosequencing. (6th January 2015) - Vanlerberghe, C.; Faivre, L.; Petit, F.; Fruchart, O.; Jourdain, A.‐S.; Clavier, F.; Gay, S.; Manouvrier‐Hanu, S.; Escande, F.
<x xml:space="preserve">Abstract</x> During limb development, the spatio‐temporal expression of sonic hedgehog (SHH) is driven by the Zone of polarizing activity Regulatory Sequence (ZRS), located 1 megabase upstream from SHH. Gain‐of‐function mutations of this enhancer, which cause ectopic expression of SHH, are known to be responsible for congenital limb malformations with variable expressivity, ranging from preaxial polydactyly or triphalangeal thumbs to polysyndactyly, which may also be associated with mesomelic deficiency. In this report, we describe a patient affected with mirror‐image polydactyly of the four extremities and bilateral tibial deficiency. The proband's father had isolated preaxial polydactyly type II (PPD2). Using Sanger sequencing, a ZRS point mutation (NC_000007.14, g.156584153A>G, UCSC, Build hg.19) was only identified in the patient. However, pyrosequencing analysis enabled the detection of a 10% somatic mosaic in the blood and saliva from the father. To our knowledge, this is the first description of a ZRS mosaic mutation. This report highlights the complexity of genotype–phenotype correlation in ZRS‐associated syndromes and the importance of detecting somatic mosaicism for accurate genetic counselling.